Development and application of triaxial rock shear - self-supporting fracture conductivity experiment system. Issue 2 (October 2021) - Xiu, Nailing; Yan, Yuzhong; Wang, Xin; Cai, Bo; Liang, Tiancheng; Fu, Haifeng
Abstract: The structure and function of shear - self-supporting fracture conductivity test device in great detail were presented. This device system consists of five parts: vertical loading system, horizontal shear loading system, the servo control system, power system, shear box and its sealing system, digital control and acquisition system. It can provide vertical force up to 2000KN, shear force 500KN, lateral stress 50MPa and hydraulic pressure 40 MPa. Characteristics of the system are illustrated as follows. (1) The experimental research of rock shear failure can be performed under three axial stress conditions, the lateral stress is loaded by hydraulic oil and the vertical stress is loaded by pressing machine. (2) True triaxial and quasi-triaxial loading modes can be switched by using different sealing sleeves. (3) The shear seepage coupling and self-supporting fracture conductivity tests could be conducted under three axial stress conditions. (4) The stress and displacement loading modes under different loading rate can be realized by servo system. Based on this experimental system, shear - fracture conductivity test under three axial stress conditions was performed on shale specimen and its reliability was verified. The experimental system can be used to provide theoretical basis for the shear destruction mechanism and Self-supporting shear fracture conductivity test under true triaxial stress conditions. The research has an important guiding significance on the formation mechanism of unconventional reservoir shear fracture and the flow capacity of self-supporting shear fracture and its influencing factors.